Augmented Reality untuk Materi Bangun Ruang Menggunakan Unity 3D, Vuforia SDK dan Aplikasi Blender - Rahmat Rahmat; Noviyanti Noviyanti (Fakultas Ilmu Komputer Universitas Almuslim Bireuen - Aceh, 2020)
The development of information and communication technology has an impact on globalization which will affect all aspects of human life, especially in the world of education. This requires educators to make innovation in learning. One of the innovations that following technological developments, namely Augmented Reality (AR). Augmented Reality is a technique of combining real and virtual worlds and is based on 3-Dimensions (3D). The objects used can be 2D or 3D. This research is entitled Augmented Reality for Building Materials using Unity 3D, Vuforia SDK, and Blender Applications. In this research, the application was developed by involving 3 main software, namely vuforia, unity 3D, and Blender. Vuforia is a plugin for a software called unity 3D. Augmented Reality and Unity 3D are two platforms that make it easier for users to produce 3D graphics that will be displayed if the graphic that has been used as a marker is highlighted with a camera from an SP. The results of this study have succeeded in developing applications with building markers using vuforia, unity 3D, and Blender.